Pelaksanaan Pengawasan Pekerja Warga Negara Asing di Diprovinsi Bali - Prabowo Wijayanto; I Nyoman Putu Budiartha; Desak Gede Dwi Arini (Fakultas Hukum, Universitas Warmadewa, 2021)
The large number of foreign workers working in Bali invites attention from the government to conduct measurable and directed supervision. In order to create administrative order, a regulation is made in the form of Permit to Hire Foreign Workers (IMTA). The purpose of this paper is to find out how the legal provisions and factors that occur in the implementation of supervision of foreign workers. From the facts that occur can be formulated the problem as follows: first, how is the implementation of TKA supervision by the Department of Labor of the Province of Bali? Second, what are the inhibiting factors? The method used in this paper is empirical, namely by conducting direct observations and interviews with sources in this case the related by Department of labor workers. Based on the results of research and discussion on the process of implementing labor inspections carried out by the Bali Provincial Manpower Office for companies that use foreign labor through granting permission to employ Foreign Workers (IMTA) in the Bali Provincial labor Office. The inhibiting factors include: TKA users neglect to intentionally not extend the IMTA, lack of coordination between the immigration office that issued a residence permit with the Bali Provincial Manpower Office or the Ministry of Manpower as the agency issuing permits to hire Foreign Workers, weak supervision and control by the local Provincial Manpower Office. Socialization caused by the unavailability of a budget from the Ministry of Manpower and Transmigration.